Molecular Biological Determination of HER2 Status Using Both DNA and RNA Approaches: A Concordance Study with IHC Assessment - Ruszova, Ema; Khaznadar, Ziad; Spurkova, Zuzana; Vlcanova, Katerina (International journal of molecular sciences, 2025)
The immunohistochemical (IHC) or fluorescence/chromogenic in situ hybridization (FISH/CISH) assays for assessing HER2 are now recommended by the American Society of Clinical Oncologists and the College of American Pathologists, but there are an increasing number of published studies describing alternative diagnoses at the molecular level. Inspired by these studies, we established a laboratory-developed test (LDT) to analyze HER2 status not only at the gene expression level but also at the gene copy number. A precise copy number calculation was fulfilled including the Control Genomic DNA of known concentration, which allowed subsequent assay validation at the DNA level. The results were reported according to the concordant results of the DNA and RNA approaches. By comparing with IHC determination, completely identical results were found in ten blank samples, which underlines the legitimacy of molecular biological approaches in this diagnostic field. An equivocal sample that was positive by IHC and qPCR was found to be negative by the FISH and so it may change the choice of personalized medicine. The topic of this short communication will hopefully contribute to allowing IVD-certified diagnostics based on the HER2 gene expression profile or copy number to be tested in the Czech Republic as well.
Keywords: Receptor, ErbB-2; Breast Neoplasms; HER2/ERBB2; quantitative PCR assessment; hybridizace in situ fluorescenční; Gene Dosage; DNA; imunohistochemie; receptor erbB-2; In Situ Hybridization, Fluorescence; RNA; Biomarkers, Tumor; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; gene expression; nádory prsu; genová dávka; Female; gene copy number; lidé